Responsabilidade civil do árbitro - Lucas, Marcus Vinicius Pereira (2018)
This paper analyses the arbitrator´s role and the duties that the arbitrator takes when accept to participate in an arbitration procedure. From this introduction, the work seeks to define the extent of arbitrators obligations, focusing in what the ethical codes and internal rules of arbitral institutions says about this duty and about preserving the impartiality and independence of the arbitrator. Although the Brazilian Arbitration Act has expressly given the arbitrators the very same treatment as the one given to Court judges for criminal law purposes, there is no specific provision regarding the civil liability of arbitrators. The second part is exposed the liability theory in Roman law, and the evolution of this institute in the Brazilian system, highlighting the possibility of state condemnation due to constitutional torts. Deals with the analogous application of the theory of civil responsibility of the judge to the arbitrator, pointing out the differences between the lawsuit and the arbitration procedure. Once defined the extent of arbitrator´s obligations and how the arbitrator may be liable, this paper will takes into account both contractual and jurisdicional aspects of the arbitrators activity